Editorial Board & Contents Vol.7-8, No.2-1, Jul 2021 -Dec 2022 - Nasiruddin, Md (The National University Journal of Humanities, Social Sciences and Business Studies, 2023)
Abstract not available NU Journal of Humanities, Social Sciences & Business Studies Vol. 7 & 8, No.2 & 1, July 2021 - December 2022 p. i-iii